ANALYSIS OF THE EFFECT OF TEACHING STAFF QUALITY, FACILITIES, AND SCHOOL LOCATION ON ELEMENTARY SCHOOL STUDENT GRADUATION RATE - Muh. Asharif Suleman (Taskuliah Edukasi Indonesia, 2025)
This study aims to analyze the influence of teaching staff, school facilities, and school location on student graduation by referring to PISA Report data. The research sample consisted of 50 students from various schools in Indonesia who participated in the PISA survey. This study used a quantitative descriptive approach with multiple linear regression analysis techniques through the assistance of JASP 0.16.1.0 software. The results of the study indicate that: (1) teaching staff has a negative and insignificant effect on student graduation; (2) school facilities have a positive and significant effect on student graduation, so that the availability of adequate facilities is proven to be an important factor in supporting learning success; (3) school location has a negative and insignificant effect on student graduation; and (4) simultaneously, teaching staff and school location do not have a significant effect on student graduation. The implications of these findings emphasize that the quality of school facilities is a key factor in supporting student academic success. Therefore, educational policy makers need to prioritize improving educational facilities and infrastructure, while schools and teachers can utilize existing facilities optimally to create a more effective learning process. This research also provides a basis for further study on how external and internal school factors can influence students' academic achievement in Indonesia.